Systemic Banking Crises Revisited - Laeven, Luc (IMF Working Papers; Working Paper, 2018)
This paper updates the database on systemic banking crises presented in Laeven and Valencia (2008, 2013). Drawing on 151 systemic banking crises episodes around the globe during 1970-2017, the database includes information on crisis dates, policy responses to resolve banking crises, and the fiscal and output costs of crises. We provide new evidence that crises in high-income countries tend to last longer and be associated with higher output losses, lower fiscal costs, and more extensive use of bank guarantees and expansionary macro policies than crises in low- and middle-income countries. We complement the banking crises dates with sovereign debt and currency crises dates to find that sovereign debt and currency crises tend to coincide or follow banking crises.